Global Analysis of a Planetary Gear Train - Tongjie Li; Rupeng Zhu (Shock and Vibration)
By using the Poincaré-like cell-to-cell mapping method and shooting method, the global characteristics of a planetary gear train are studied based on the torsional vibration model with errors of transmission, time-varying meshing stiffness, and multiple gear backlashes. The study results reveal that the planetary with a certain set of parameters has four coexisting periodic orbits, which are P-1, P-2, P-4, and P-8, respectively. P-1 and P-2 motions are not of long-term stability, P-8 motion is of local stability, and P-4 motion is of global stability. Shooting method does not have the capacity of searching coexisting periodic orbits in a global scope, and it is easy to omit some periodic orbits which are far away from the main gropes of periodic orbits.